(untitled) (Journal of Organizational Psychology, 2021)
Meaning-centered education (Kovbasyuk & Blessinger, 2013) suggests that students benefit from incorporating learning outcomes from non-cognitive domains. A radical idea in a world focused on standardization, this paradigm nevertheless holds great value for educators and students alike as we can never “find a behaviour or a state which is purely cognitive without affect nor a purely affective state without a cognitive element” (Piaget as cited in Clark & Fiske, 1982, p.130). Infusing an online curriculum with weekly formative assessment activities allowed instructors to monitor students’ states of mind while reducing negative emotional effects on learning by incorporating that feedback. Extended analysis promoted a deeper understanding of the roles that emotions and attitudes play in achieving affective learning outcomes.